Achievements in Hypothyroidism Treatment with Herbal Medicine: A Systematic Review of Randomized Controlled Trials - Javidi, Najmeh; Khorasani, Zahra M.; Salari, Roshanak; Niroumand, Shabnam; Yousefi, Mahdi (Current Drug Discovery Technologies, 2023)
Background: Hypothyroidism is a common endocrine disease in the world that causes morbidity and mortality due to its association with metabolic diseases, especially in old age, and longterm treatment with levothyroxine causes many side effects for patients. Treatment with herbal medicine can regulate thyroid hormones and prevent side effects. Objective: The purpose of this systematic review is the evaluation of the effect of herbal medicine on the signs and symptoms of primary hypothyroidism. Methods: PubMed, Embase, Google Scholar, Scopus, and Cochrane Central Register of Controlled Trials were searched until 4 May, 2021. We selected randomized clinical trials (RCTs) that have assessed the effect of herbal medicine on hypothyroidism. Results: Out of 771 articles, 4 trials with 186 participants were included. In one study, Nigella sativa L. caused a significant decrease in weight (P=0.004) and body mass index (BMI) (P=0.002). TSH levels were reported to be decreased and T3 increased in the treatment group (P =0.03) (P=0.008), respectively. In another study on Nigella sativa L., results did not show a significant difference between the two groups (p=0.02). A significant decrease in total cholesterol (CHL) and fasting blood sugar (FBS) was reported in participants with negative anti-thyroid peroxidase (anti-TPO) antibodies. In patients with positive anti-TPO antibodies, a significant increase in total cholesterol and FBS was observed in the intervention group (p=0.02). In the third RCT, T3 in the ashwagandha group at 4 and 8 weeks significantly increased by 18.6% (p=0.012) and 41.5% (p < 0.001), respectively. A noticeable increase was found in the T4 level from baseline by 9.3% (p= 0.002) and 19.6% (p < 0.001) at 4 and 8 weeks, respectively. TSH levels fell remarkably in the intervention group compared to placebo at 4 weeks (p <0.001) and 8 weeks (p <0.001), respectively. In the last article selected, Mentha x Piperita L. showed no significant difference in fatigue scores between intervention and control groups at the midpoint (day 7), while fatigue scores improved in the intervention group in all subscales compared to the control group on day 14. Conclusion: Some herbal remedies, including Nigella sativa L., ashwagandha, and Mentha x Piperita L., can improve the signs and symptoms of primary hypothyroidism, but using a more extensive and advanced methodology will provide us with more complete results.
Keywords: traditional medicine